ANALISIS METODE ROLE PLAYING DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA - Wiyudia, Nasya; Siti Rokmanah; Encep Andriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Speaking is one of the most important language skills and is often used in a variety of everyday situations. However, students' speaking skills are still relatively low due to a lack of confidence and limited access to support resources in the learning process. To overcome this problem, the role-playing method can be applied as an effective active learning approach to improve speaking skills. The purpose of this study is to evaluate the effectiveness of the role-playing method in improving students' speaking skills at the elementary school level. This research was conducted by a literature review method to analyze relevant publications on Google Scholar. Based on the results of the review, the role-playing method proved to be an interesting, innovative, and highly effective learning strategy in developing speaking skills in elementary school students.